Multi-site project organisation knowledge sharing ontology - Dong, Hai; Hussain, Farookh; Chang, Elizabeth (IEEE Computer Society, 2007)
The implementation of ontology starts to step into the field of project organizations. With the appearance of project outsourcing, the location of project workplace becomes increasingly multiple, which challenges the administration of senior management to projects. In this paper, we analyze the daily knowledge sharing activities, including the organizational structure, the procedure of project planning and the scenarios of project distribution, by a case study in City of Melville Council -- a typical multi-site project organization, to discover the issues in these activities. By means of extending the theory of CCCI Metrics into the field of project management, we design the multi-site project track and trace ontology, in order to promote the knowledge sharing activities between senior management and project groups.